Manualidades en foamix y su incidencia en el desarrollo de la motricidad fina a estudiantes de la escuela de educación básica veinticuatro de Mayo, cantón Milagro, provincia Guayas - Sánchez Zambrano, Mery del Pilar (2017)
The final report of this research project contains very important aspects to strengthen the cognitive development of the Students of the School of Basic Education Twenty-four of May, through the handcrafts elaborated in foamix, which is one of the strategic forms for the development of the fine motor skills, taking it as the best results of the autonomous work of the student and her teacher. This investigative work called, Crafts in foamix and its incidence in the development of fine motor skills to students of the School of Basic Education Veinticuatro de Mayo, canton Milagro, province of Guayas, that after detecting the problem that was presented in the students, we formulated clear objectives, both general and specific, precise, measurable and achievable by implementing a teaching-learning system to keep pace with the demands of science and technology, which we now have to be prepared for. In this final report based on a research process, it has been based on a theoretical and referential framework, in which we have learned the most important concepts taken as a basis for the development of fine motor skills, with a statistical analysis that helped us to learn about the great problems of motor skills of children, and then give them possible solutions, through a proposal called "Didactic guide of crafts in foamix to motivate the development of fine motor skills in students; based on bibliographic means that will allow reaching the expected results.